Average symptom trajectories following incident radiographic knee osteoarthritis: data from the Osteoarthritis Initiative. Issue 2 (4th July 2016) - Whittle, Rebecca; Jordan, Kelvin P; Thomas, Elaine; Peat, George
Abstract : Introduction: Previous research has identified the existence of a prodromal phase of symptom worsening beginning on average 2–3 years prior to the first appearance of radiographic knee osteoarthritis (OA). The current study extends these observations to investigate the trajectory of self-reported pain, stiffness, function and other symptoms following the incidence of radiographic OA. Methods: Data were from the incidence cohort of the Osteoarthritis Initiative public use data sets. Cases were defined as knees without symptoms at enrolment, which developed incident radiographic OA (Kellgren and Lawrence grade ≥2) at any of the first 4 annual follow-up visits. Symptoms investigated were knee-specific Western Ontario & McMaster Universities Osteoarthritis Index and Knee injury and Osteoarthritis Outcome Score subscale scores and individual items, available up to 3 years before and 5 years after the incidence of radiographic OA. Trajectories of having at least one of the symptoms from a subscale, and for each individual symptom over time, were fitted using multilevel logistic regression models. Results: The probability of symptoms following the initial prodromal phase generally stabilised, whereas the probability of moderate, severe or extreme symptoms was consistently low. Two exceptions were pain frequency, which increased greatly in the lead up to incidence, then decreased slightly, and audible joint sounds, which had a much higher overall probability, and after increasing prior to incident radiographic OA, stabilised then started to increase again at 5 years. Conclusions: Following an increase in the risk of symptoms during the prodromal phase, this risk does not continue to increase in the period up to 5 years after the incidence of radiographic OA.